Linear parameter varying control of a doubly fed induction generator based wind turbine with primary grid frequency support. (25th June 2013) - Wang, Chen; Weiss, George; Edwards, Christopher; Marcos, Andres; Balas, Gary
SUMMARY This paper proposes a control method for a doubly fed induction generator (DFIG) driven by a wind turbine, whose rotor is connected to the power grid via two back‐to‐back pulse‐width modulation power converters. First, we design a rotor current controller for this system using the linear matrix inequality based approach to linear parameter varying systems, which takes into account the nonlinear dynamics of the system. We propose a two‐loop hierarchical control structure. The inner‐loop current controller, which considers the synchronous speed and the generator rotor speed as the components of the parameter vector, achieves tracking of the rotor current reference signals. The outer‐loop electrical torque controller aims for wind energy capture maximization and also grid frequency support, and it generates the reference rotor current. We perform a controller reduction for the inner‐loop linear parameter varying controller, which is not doable by conventional model‐reduction techniques, because the controller is parameter dependent. In simulation, the reduced‐order controller has been tested on a nonlinear fourth‐order DFIG model with a two‐mass model for the drive train. Stability and high performance have been achieved over the entire operating range of the DFIG in the wind turbine. Simulation results have demonstrated the capability of the proposed two‐loop control system to implement also grid frequency support. Copyright © 2013 John Wiley & Sons, Ltd.